Advances in the Diagnosis and Treatment of Thyroid Carcinoma - Medas, Fabio; Alesina, Pier Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is related to the latest research in the field of thyroid surgery, including molecular and imaging diagnosis, surgical treatment, and the treatment of recurrent disease and advanced thyroid carcinoma.